Building up relationships in asymmetric co-operation games between the cleaner wrasse Labroides dimidiatus and client reef fish - Bshary, Redouan (My University, 2002)
It has been suggested that individuals may prevent partners from cheating by building up relationships slowly, giving very little in the beginning and raising the stakes in subsequent moves if partners reciprocate. I tested this idea with field experiments on the cleaner-fish Labroides dimidiatus and its "client" reef fish. Clients visit cleaners at their small territories, so-called cleaning stations, to have parasites removed. Cleaners were first observed and then caught and either put back on their original territory or moved to a new site. I noted a variety of cleaner and client behaviour to evaluate how, if at all, relationships are built up. Cleaners and resident clients indeed build up relationships, but with heavy initial investment. There was no evidence that cleaners build up relationships with client species that have access to several cleaners. Finally, it appeared that cleaners constantly invest in relationships with predatory clients, possibly to reduce the risk that predators try to catch them. I propose that asymmetries between partners with respect to either payoff values or strategic options are the major reason why the results do not fit the so-called raising-the-stakes strategy.
Keywords: Labroides dimidiatus; Cooperation; Mutualism; Prisoner's dilemma; Asymmetric game